Problema de Steiner Euclidiano aplicado a mol??culas de interesse biol??gico - Amorim Neto, Alcides de Castro (2015)
Made available in DSpace on 2015-04-22T22:16:13Z (GMT). No. of bitstreams: 1 Alcides de Castro Amorim Neto.pdf: 1160215 bytes, checksum: 9d45c01bd11518c19b4c0577a41c7455 (MD5) Previous issue date: 2007-05-26